Формування української правової доктрини щодо кваліфікації кримінальних правопорушень, учинених організованими злочинними угрупованнями, у контексті змін кримінального законодавства - Птащенко, Дмитро Сергійович (Київський національний університет імені Тараса Шевченка, 2021)
Досліджено проблеми формування доктрини права щодо кваліфікації кримінальних правопорушень, учинених організованими злочинними угрупованнями, у зв'язку зі змінами кримінального законодавства України протягом 2020–2021 років. Здійснено системний аналіз і сформульовано основні висновки щодо впливу впровадженого інституту кримінальних проступків на кваліфікацію кримінальних правопорушень, учинених організованими злочинними угрупованнями. Висвітлено основні законодавчі зміни ст. 255 Кримінального кодексу України "Створення, керівництво злочинною спільнотою або злочинною організацією, а також участь у ній" відповідно до Закону України "Про внесення змін до деяких законодавчих актів України щодо відповідальності за злочини, учинені злочинною спільнотою". Також сформульовано основний зміст юридичних складів злочинів, специфічна часть яких передбачена частинами 1–5 ст. 255 Кримінального кодексу України; установлено обсяг і зміст понять "злочинна спільнота", "створення злочинної організації, керівництво такою організацією або її структурними частинами", "участь у злочинній організації", "створення злочинної спільноти", "керівництво злочинною спільнотою". Наведено характеристику співвідношення юридичних складів злочинів, специфічна частина яких передбачена частинами 1–5 ст. 255 Кримінального кодексу України. Сформульовано основні правила кримінально-правової кваліфікації юридичних складів злочинів, специфічна частина яких передбачена частинами 1–5 ст. 255 Кримінального кодексу України. Указано на необхідність формування специфічного підходу до кримінально-правової кваліфікації кримінальних проступків, учинених організованою групою або злочинною організацією, оскільки ця проблема не вирішується в нормативній площині й нині є питанням практики застосування кримінального права та доктрини кримінального права.

The Article 1 of the Constitution of Ukraine regulates: Ukraine is a sovereign and independent, democratic, social, legal state. One of the destabilizing factors in building the rule of law is the commission of criminal offenses by organized criminal groups. Due to the changes in the criminal legislation during the last two years, the criminal law norms have undergone significant changes, which directly or indirectly affect the qualification of criminal offenses committed by organized criminal groups. Given the changes in criminal law, the qualification of criminal offenses committed by organized criminal groups requires uniform systemic approaches, primarily at the level of judicial law enforcement practice. The formation of the Ukrainian legal doctrine on the qualification of criminal offenses committed by organized criminal groups is one of the significant auxiliary guidelines in the formation of such law enforcement practice. To achieve this goal and the defined objectives, the following methods were applied in the study: logical and normative – for the analysis of criminal law on the qualification of criminal offenses committed by organized criminal groups; system analysis – when considering judicial law enforcement practice (first of all, the Supreme Court and the Supreme Court of Ukraine) of the qualification of criminal offenses committed by organized criminal groups. The legislation strengthens criminal liability for criminal offenses by organized criminal groups, in particular, as evidenced by the amendments to the Criminal Code under the Law of Ukraine "On Amendments to Certain Legislative Acts of Ukraine on Liability for Crimes Committed by the Criminal Community" dated by the 4th of June 2020. Before the formation of new approaches to the doctrine of criminal law and law enforcement judicial practice on the qualification of criminal offenses (crimes), a specific part of which is provided by h.ch. 1-5 art. 255 of the Criminal Code, the indirect reference is the provision of the resolution of the Plenum of the Supreme Court of Ukraine of December 23, 2005 №12 "On the practice of consideration by courts of criminal cases on crimes committed by stable criminal groups."
Formation of the Ukrainian legal doctrine concerning qualification of the criminal offenses committed by the organized criminal groups
Keywords: кримінальні проступки; злочинна спільнота; злочинна організація; організована група; створення злочинної спільноти; керівництво злочинною спільнотою; організовані злочинні угруповання; criminal offenses; criminal community; criminal organization; organized group; creation of a criminal community; leadership of a criminal community; organized criminal groups